ヒョウカイ コウコウ セミナー ホウコク - 吉田, 栄夫; ヨシダ, ヨシオ; Yoshida, Yoshio (1985)
P(論文) 1984年10月12日, 国立極地研究所で所内外の関係者約70名の参加を得て氷海航行セミナーが開催された。これは船舶の氷海航行に関して科学的, 技術的問題点を探り, 従来の資料の分析, 現在の調査技術の検討などを通じて, 今後の研究の方向性を模索し, 科学的基礎の確立を目指す第一歩として行われたものである。海氷の両極における地域的特性やその調査方法, 実際の氷海における船舶の運用, 船舶工学と海氷の性質, リモートセンシングによる海氷の探査などについて話題提供と討議が行われ, 当初の目的が達成された。 The First Seminar on the Problems of Ice Navigation was held at National Institute of Polar Research on October 12th, 1984. The objective was to review the present scientific knowledge of sea ice and technological problems relating to ice navigation, in particular in the Antarctic, and to seek the possibility of cooperative research on ice navigation in scientific and technological aspects. Discussed subjects were as follows : 1) Distribution and characteristics of sea ice and survey methods, 2) Sea ice characteristics in the vicinity of Lutzow-Holm Bay revealed from satellite image analysis, 3) Ice navigation of icebreakers FUJI and SHIRASE, 4) Sea ice problems in the shipbuilding technology, 5) Sea ice observation by remote-sensing techniques, 6) Sea ice thickness measurement by an impulse radar. Results of discussion were useful as a basis for future research. departmental bulletin paper